2011
DOI: 10.1007/s11368-011-0405-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing phosphorus availability in phosphorus-fertilized zones by reducing phosphate adsorbed on ferrihydrite using rice straw-derived biochar

Abstract: Purpose Biochar amendments can alter phosphorus (P) availability in soils, though the influencing mechanisms are not yet fully understood. This work investigated the adsorption and desorption of P on ferrihydrite (F, a Feoxide widely distributed in surface environments) in order to evaluate the interactions between P and Fe-oxide in the absence or presence of biochar (F or ferrihydrite-biochar (F-B) interaction) in soils. Materials and methods Biochar was produced by pyrolysis of rice straw at 600°C in steel r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
89
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(104 citation statements)
references
References 31 publications
13
89
0
2
Order By: Relevance
“…According to Khan and Joergensen (2012) and Agegnehu et al (2016), the incorporation of biochar and compost in soil could potentially improve P availability and significantly stimulate P uptake by ryegrass and maize plant, respectively. This was probably due to biochar's liming effects that decreased P fixation by Al and Fe oxide in the soil (Yuan and Xu 2011;Cui et al 2011). In this study, notable pH improvement was observed especially in biochar-compost amendment (pH 6.6) as compared to control treatment (pH 4.4).…”
Section: Discussionmentioning
confidence: 53%
“…According to Khan and Joergensen (2012) and Agegnehu et al (2016), the incorporation of biochar and compost in soil could potentially improve P availability and significantly stimulate P uptake by ryegrass and maize plant, respectively. This was probably due to biochar's liming effects that decreased P fixation by Al and Fe oxide in the soil (Yuan and Xu 2011;Cui et al 2011). In this study, notable pH improvement was observed especially in biochar-compost amendment (pH 6.6) as compared to control treatment (pH 4.4).…”
Section: Discussionmentioning
confidence: 53%
“…These results are consistent with those of Sarker et al (2014) who determined that an increase of plant-available P status may be related to increase in mineralization of organic P as affected by lime. Also, the obtained results could be explained by the relatively good correlation between organic matter and phosphorus by the interaction of oxides with organic matter that considerably reduces phosphorus binding sites in the former and increases the amount of plant-available P (Heredia, Cirelli, 2007;Cui et al, 2011).…”
Section: Resultsmentioning
confidence: 97%
“…Overall, manure-and sludge-based BCs are richer in plant available nutrients as compared to grass-and wood-based BCs, which is mostly a reflection of their original feedstock properties, although C, N, and S losses at high PTs are unavoidable Jensen, 2013b;Subedi et al, 2015Subedi et al, , 2016aSubedi et al, , 2016b. Other nutrients (P, K, Ca, Mg, and Na) found mainly in the ash fraction, are plantavailable depending on the soil-BC matrix, pH, and the presence of chelating substances that regulate their mobilisation (Cui et al, 2011;Wang et al, 2015). Nitrogen content and availability correlates highly to PT, rate of heating, and feedstock type and composition (Wang et al, 2012a;Clough et al, 2013;Subedi et al, 2016b).…”
Section: Referencesmentioning
confidence: 99%